Hubungan Pengetahuan Pasien dengan Perilaku Pencegahan Hiperglikemia pada Penderita Diabetes Melitus - Ostri Nia Epi Majore; Sarwan Sarwan; Rahmat H. Djalil (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Diabetes Mellitus is a chronic disease characterized by increased blood glucose sugar levels or referred to as hyperglycemia. The purpose of this study was to find out the correlation between patient knowledge and hyperglycemia prevention behavior in patients with diabetes mellitus in the Mangaran Health Center Working Area. This study used an analytic descriptive method with a cross sectional method approach. The instrument used was a questionnaire, of patient knowledge about hyperglycemia prevention and hyperglycemia prevention behavior, then the data that had been collected was tested using the chi square test. The results of the study include good knowledge and the results of research based on good preventive behavior. Bivariate data data analysis obtained results by using the chi square test. Regarding the independent variable and the dependent variable, the p- value = 0.002 (α ≤ 0,05). The conclusion in this study is that there is a significant correlation between patient knowledge and hyperglycemia prevention behavior in patients with diabetes mellitus. The suggestion in this research is that this research is expected to be a source of information for patients about public knowledge due to hyperglycemia and preventive behavior.